The role of micro-RNA in the diagnosis of HIV-associated immune reconstitution inflammatory syndrome - Meyer, Pieter Willem Adriaan (University of Pretoria, 2025)
Dissertation (MSc (Medical Immunology))-- University of Pretoria, 2024.